Factors affecting demand for modern contraceptives among currently married reproductive age women in rural Kebeles of Nunu Kumba district, Oromia, Ethiopia - Alemu Kebede; Sileshi G. Abaya; Elias Merdassa; Tariku Tesfaye Bekuma (BMC, 2019)
Abstract Background Family planning plays a key role in improving the health of the mother and the child. Yet there are still significant levels of demand for family planning that are unmet and these can lead to unintended pregnancy. So, women's demand for contraceptive utilization to limit, space, or delay the number of family size can be increased by integrating family planning service at each service delivery points. Objective The main aim of this study was to assess the demand for modern contraceptive and associated factors among currently married women of the reproductive age group in rural kebeles of Nunu Kumba District, 2015. Methods A community-based cross-sectional study design was conducted from January 15-30, 2015 among 584 systematically selected currently married women of reproductive age in six rural kebeles of Nunu Kumba District. A pre-tested and interviewer-administered questionnaire was used to collect the data. Data were analyzed using SPSS version 20. Descriptive statistics were done to summarize the data. A multivariate logistic regressions analysis method was employed and odds ratio with 95% confidence interval was used to control for possible confounders. P-value < 0.05 was used to declare a significant association. Results The total demand for modern methods of contraceptive was 450 (77.1%) of which 325 (55.7%) of them were current user and 125 (21.4%) of them were had unmet need for modern contraceptive methods. Being in the younger age group (15-24 and 25-34 years [AOR = 0.196; 95% CI: 0.055, 0.692] and [AOR = 0.179, 95% CI: 0.043, 0.745] respectively, husband having no intention for more children [AOR = 4.124, 95% CI: 1.891, 8.996], number of children alive [AOR = 2.617, 95% CI: 1.056, 6.486], and couples ever not discussed on family planning [AOR = 0.340, 95% CI: 0.187, 0.619] were factors associated with demand for modern methods of contraception. Conclusion The total demand for modern methods of contraceptive was high in the study area except for long-acting and permanent methods with high unmet need for spacing than for limiting. Therefore, any program aimed at promoting family planning at the district level should look for ways and means of increasing demand for long-acting and permanent family planning methods and encouraging husband involvement to increase its utilization.